Additives and / or additive-additive combinations used for blending, thermoplastic synthetic materials having them, and the uses of synthetic materials.
By mixing the combination of conductive and magnetic additives into the synthetic materials, especially carbon fiber and magnetite, as well as high iron powder, the problem of poor electric and magnetic field shielding in the synthetic materials is solved, and efficient EMI shielding is achieved. It has the characteristics of lightweight and good adaptability.
Patent Information
- Application Number
- CN202180036294.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-10-23
- Filing Date
- 2021-05-20
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2041-05-20
AI Technical Summary
The prior art is difficult to achieve efficient electric and magnetic field shielding in synthetic materials, especially in magnetic fields, with poor shielding effects.
Synergistic effects are achieved to enhance the shielding effect of the magnetic field by mixing the combination of conductive additives and magnetic additives, especially the combination of carbon fiber and magnetite, and high content of iron powder.
It achieves a high shielding effect in both electric and magnetic fields, with a shielding degree of more than 20dB, suitable for EMI applications, and has higher design freedom and adaptability than metal shells or metal claddings.
Smart Images

Figure BDA0003949762420000051 
Figure BDA0003949762420000061 
Figure BDA0003949762420000091
Abstract
Description
Technical Field
[0001] The invention relates to an additive and / or an additive-additive combination for admixture into a synthetic material, preferably a thermoplastic synthetic material, in order to impart EMC shielding properties to the synthetic material, wherein according to the invention both the electric field and the magnetic field are shielded, in particular both are also greater than 20 dB. The invention also relates to a thermoplastic synthetic material into which such an additive and / or an additive-additive combination is admixed. The invention also relates to the use of such a thermoplastic synthetic material, in particular for the production of X-ray detectable objects. Background Art
[0002] Electronic components and devices are generally designed to be electromagnetically compatible so that they do not interfere with other devices or are interfered with by other devices due to unwanted electrical or electromagnetic effects. First of all, the frequencies that need to be shielded are between 30 kHz and approximately 5 GHz, where this range is also generally referred to as high-frequency radiation. These frequencies appear in the fields of radio broadcasting, television, aviation and maritime or police radio, GPS, UMTS, Bluetooth and Wifi, and therefore also in mobile phones and smartphones, as well as in radar measurements and non-destructive material testing. This electromagnetic compatibility is usually achieved by electromagnetic interference (EMI) shielding housings, in particular also by synthetic material housings, and here not only the components and devices themselves are protected from external radiation, but also their environment is protected from the electromagnetic radiation emitted by them.
[0003] Shielding or attenuation of electromagnetic radiation, in particular in magnetic fields, is generally difficult to achieve. For example, it is known in the automotive sector to use metal housings or plastic housings with metal coatings to provide EMI shielding for electronic components. However, these housings are heavy on the one hand and have disadvantages compared to plastics, at least in terms of freedom of design, on the other hand, which makes them unsuitable for every installation situation. Metal coating for EMI shielding is carried out, for example, by aluminum die casting or PVD coating of the component to be shielded or coating with metal-containing pigments.
[0004] Generally speaking, the degree of shielding that can be achieved also depends on the wall thickness of the housing or the outer casing of the device / component to be shielded and the wavelength range of the frequency to be shielded.
[0005] In order to achieve EMI shielding in synthetic materials, it is known in the prior art, inter alia, to mix the following substances into the following synthetic material matrices:
[0006] - mixing dolomite into PA or PE, and mixing granite into styrene copolymers (EP 1 127 917 B1);
[0007] - Mixing bronze or brass into PA or into a combination of PC and ABS (KR 2002 068 248 A);
[0008] - steel fibres or steel fibres provided with a nickel-copper coating;
[0009] - Mixing CuO, CuCl2, Cu(OH)2 into PA (WO 2014 163 242 A1);
[0010] - mixing magnetite into PA (DE 100 08 473 A1);
[0011] - silver-coated glass fibers or glass spheres, concentrically staggered carbon nanotubes (multi-walled carbon nanotubes, MWCNT) - also with a metal coating - (DE 10 2017 200 448 A1); and
[0012] - Mixing SiC into PC and ABS (WO 2009 083 914 A1).
[0013] These components, collectively referred to as additives, are further referred to as conductive additives and magnetic additives, respectively, where conductive additives refer to components with a magnetic content of less than 10 4 Ohm's volume resistance, magnetic additives refer to those with magnetic properties.
[0014] Here, EMI shielding is measured in the electric field in accordance with the standards ASTM D 4935 or IEC 62153-4-4 Ed2. The latter standard describes the measurement of attenuation in the electric field in the frequency range of 30 to 3000 MHz, the former in the range of 30 to 1500 MHz. The sample to be measured in the electric and magnetic fields is arranged in a shielded room between the transmitting and receiving antennas, and the electromagnetic radiation passing through the component is measured in both fields. Summary of the invention
[0015] The object of the present invention is to provide composites which have an increased shielding effect in electric and magnetic fields, preferably >20 dB, and can therefore be used particularly effectively in EMI applications. 20 dB of shielding corresponds to shielding of approximately 99% of electromagnetic radiation. This degree of shielding relates to wall thicknesses of 1 mm to 4 mm, preferably 2 mm, since these wall thicknesses cover most objects made from the composite according to the invention.
[0016] According to the invention, it was found surprisingly that in certain combinations of conductive additives and magnetic additives, a synergistic effect occurs, which leads to an enhancement of the shielding effect in the magnetic field, which exceeds the shielding effect of the simple addition of the corresponding additives. Surprisingly and only in certain cases, the combination of magnetic additives with conductive additives in certain synthetic materials enhances their shielding effect against the magnetic field and thus improves the shielding of the corresponding synthetic material provided against the magnetic field. As the applicant was also able to find, the magnetic additives found in particular according to the invention, when they are mixed into the thermoplastic synthetic material according to the invention, depending on their respective magnetic type and in particular also on their particle size (D50 value) and also due to the combination with the conductive additive, not only shield the electric field, but also excessively shield the magnetic field. Surprisingly, the applicant has confirmed that the combination of two magnetic additives also leads to a synergistically enhanced shielding in the magnetic field that exceeds the simple addition.
[0017] The invention makes it possible with great advantage to use a composite to which corresponding, commercially readily available additives (collectively referred to as additives, in particular additives for the matrix composite) are added in order to surprisingly achieve particularly high magnetic shielding in a simple manner. Compared to metal shells or metal-clad shells, the composite housings made of the composite according to the invention have the advantage of reduced weight, which is particularly important for use in electric vehicle components. In addition, they offer a high degree of freedom in object design when forming components made therefrom and therefore offer a high degree of adaptability to a variety of installation or use environments.
[0018] Based on their internal structure and their physical and chemical properties, suitable synthetic materials that can be used according to the invention include in particular amorphous synthetic materials, such as PC, ABS and PC-ABS combinations, and / or partially crystalline synthetic materials, preferably PA, PA6, PA66 and PA610, but also PPS. A great advantage is that basic synthetic materials that are not optimized for EMI applications can therefore be used for the admixture of the additives according to the invention, or can be made suitable for EMI applications by the admixture of these additives, so that EMI shielding components can be produced very well from the synthetic materials according to the invention.
[0019] In particular carbon fibers (CF) in combination with magnetic additives belong to the additive package according to the invention.
[0020] Furthermore, according to the invention, a single ferromagnetic additive, in particular 325 mesh iron powder, can improve magnetic shielding at an extremely high, technically not easily achievable, weight fraction of 70-80 weight % of the total composite of additive and base synthetic material or synthetic material matrix.
[0021] In another embodiment of the present invention, a synergistic effect from the combination of conductive additives and magnetic additives can be achieved for the following combinations:
[0022] -15% CF + 40% natural magnetite, particle density 5.2g / cm 3 , magnetite content ≥98.1%, D50=17μm, mixed into PC+ABS;
[0023] -15% CF + 60% 325 mesh iron powder is mixed into PA6.
[0024] Surprisingly, in the case of these combinations, higher shielding in the magnetic field is achieved than with the corresponding individual additives.
[0025] It is also surprising that for PPS with 80% 325 mesh ferromagnetic iron powder added, the high shielding effect achieved according to the invention, in particular against magnetic fields, is achieved.
[0026] The same applies to a 1:1 mixture of polyamide PA66 with paramagnetic aluminum silicate and ferrimagnetic ferro-aluminoseladonite, a special type of mica; with this combination of additives, shielding in magnetic fields of >25 dB can be achieved.
[0027] According to the present invention, surprisingly high EMI shielding behavior is also achieved for PPS and PA66 when using the above-mentioned blending of additives.
[0028] According to the invention, by mixing 80% or 70% of 325 mesh ferromagnetic iron powder into PC+ABS and PA6, respectively, shielding values in both fields are also achieved>>20dB (and for 70%, the shielding value>20dB). According to the invention, it is particularly preferred that the particle size of the mixed iron powder is D50≤45μm.
[0029] According to the present invention, mixing λ5% Ag-Cu-20 (D50: 8-13 μm, diamagnetic plate-shaped copper particles with 20% diamagnetic silver coating) and 33.33% Plasticyl PC1501 (5% pure diamagnetic MWCNT fraction) in PC+ABS also leads to a synergistic effect of MWCNT on the magnetic field of plate-shaped copper particles Ag-Cu-20, which has an enhanced shielding effect on the magnetic field relative to a single additive. The material is known in DE 10 2017 209 357.9, the content of which is hereby expressly incorporated by reference into the disclosure of the present patent application.
[0030] All other combinations according to the invention of conductive additives and magnetic additives lead to shielding in the electric and magnetic fields of more than 20 dB, respectively, i.e. EMI shielding, but no synergistic improvement in the shielding of the magnetic field. In other words, the shielding values for the electric field correspond to the shielding effect of the conductive additive, and the shielding values for the magnetic field correspond to the shielding effect of the magnetic additive.
[0031] The applicant has found that according to the present invention, the particle size-dependent D50 value of the magnetic additive to be used is a decisive parameter for its suitability for cooperative shielding, and therefore according to the present invention, the D50 value of the magnetic additive for influencing the shielding effect in the magnetic field is selected in a targeted manner in order to prepare such an additive according to the present invention.
[0032] In another advantageous embodiment of the present invention, PA and PPS are respectively used as matrix synthetic materials, and the additives are added thereto as additives. Here, according to the present invention, it has been proven that the combined addition of carbon fibers and magnetite is particularly effective for shielding.
[0033] According to the invention, in PA as the synthetic material, the combined addition of carbon fibers and iron powder and / or carbon fibers and magnetite proved to be particularly effective for shielding. In PPS as the matrix synthetic material, without the addition of carbon fibers, 80% and 70% of 325 mesh ferromagnetic iron powder were added according to the invention, whereas the combination of carbon fibers and gas-atomized ferrite steel powder surprisingly did not provide particularly effective shielding.
[0034] In this context, it is particular that in the case of PA6 as synthetic material additives are used which have a D50 value of ≤45 μm.
[0035] Magnetic additives suitable for use within the scope of the present invention come from the range of diamagnetics, paramagnets, ferromagnets and ferrimagnets, which have a high magnetic susceptibility (χ500-3000) to a partly extremely high magnetic susceptibility (χ10000-50000). In particular, the following magnetic additives can be regarded as within the scope of the present invention, wherein, if possible, the value of the magnetic susceptibility χ is mentioned after the magnetic additive in each case:
[0036]
[0037]
[0038] Advantageously, the thermoplastic synthetic material according to the invention has admixed additives in the form of magnetic additives and / or in the form of a combination of magnetic additives and conductive additives which are suitable and can be used to achieve X-ray detectability of products produced therefrom.
[0039] The following magnetic additives are particularly suitable within the scope of the invention, and their mixing fractions, if applicable, preferred mixing fractions, their D50 values and their magnetic properties are indicated in each case:
[0040] 1) Manganese sulfate 15-25%, D50: none, paramagnetic;
[0041] 2) CuSn10 0-25% with uncertain particle shape, D50: 64.4μm, diamagnetic copper alloy;
[0042] 3) CuZn30 0-25% with uncertain particle shape, D50: 240 mesh, diamagnetic copper alloy;
[0043] 4) Copper (II) oxide 0-50%, preferably 15-45%, D50: 23.9 μm, diamagnetic ceramics and semiconductors;
[0044] 5) 325 mesh iron powder 15-85%, preferably 55-85%, D50: ≤45μm, ferromagnetic;
[0045] 6) Gas atomized ferrite steel powder 15-85%, preferably 55-85%, D50: 20-53 μm, ferrimagnetic;
[0046] 7) Natural magnetite (iron oxide / iron ore) 15-65%, particle density 5.2g / cm 3 , ≥98.1% magnetite content, D50: 17μm, ferrimagnetic;
[0047] 8) Alumina (aluminum ceramics) 65-75%, Al2O3 content> 99.5%, D50: 1.6μm, paramagnetic;
[0048] 9) Anhydrous aluminum silicate (aluminum ore) treated with aminosilane, 35-45%, Al2O3 content 42.1-44.3%, SiO2 content 51.0-52.4%, TiO2 content 1.56-2.5%, D50: 1.4μm, paramagnetic;
[0049] 10) Dolomite (calcium magnesium ore) 35-45%, D50: 2.4-3.0μm, whiteness Ry ≥ 93.5%, paramagnetic;
[0050] 11) Aluminum silicate + ferroaluminum chalcanthite (iron ore) 10-20% respectively; the above (so) + mica, D50: 4.2μm, ferrimagnetic;
[0051] 12) Ag-Cu-20 (Plate-like copper particles with 20% silver coating) 5-10%, D50: 8-13 μm, Diamagnetic + Plasticyl PC1501 (2-5% pure diamagnetic MWCNT fraction) 13.33-33.33%.
[0052] The following combination of a magnetic additive and a conductive additive is particularly suitable within the scope of the invention, wherein the respective conductive additive is carbon fiber with a weight fraction of 10% to 20% by weight and the magnetic additive is:
[0053] - Magnetite, with a weight fraction of 35% to 65% by weight and a particle density of 5.2 g / cm 3 , magnetite content ≥ 98.1% and D50 value 17μm; or
[0054] - 325 mesh iron powder, with a weight fraction of 55 wt% to 65 wt% and a D50 value of ≤ 45 μm; or
[0055] - Gas atomized ferrite steel powder with a weight fraction of 55 to 65% by weight and a D50 value of 20-60 μm; or
[0056] - Manganese zinc ferrite, with a weight fraction of 35 to 65% by weight and a D50 value of 250-315 μm.
[0057] Preferably, within the scope of the present invention, the particle size of the magnetic and / or conductive additive, expressed as the D50 value, is 10-60 μm and / or 250-315 μm for ferrimagnetic additives, ≤45 μm in the case of ferromagnetic additives, in order to achieve an ideal magnetic field shielding, and <3 μm in the case of paramagnetic additives, in order to achieve an ideal magnetic field shielding. In particular, according to the present invention, aluminum oxide, dolomite, aluminum silicate, ferromagnetite are selected within this size range. Alternatively, the particle size of the paramagnetic additive according to the present invention is 10-20 μm.
[0058] For diamagnetic additives, within the scope of the present invention, ideal shielding behavior in magnetic fields can be achieved in combination with multi-walled carbon nanotubes (MWCNTs) with a D50 value of 8-13 μm (D50 value of Ag-Cu-20, 20% silver coating on plate-shaped copper particles).
[0059] In the context of the present invention, in the case of other antimagnetic additives in combination with carbon fibers, the particle size is preferably 8-13 μm in order to achieve optimal shielding in both fields.
[0060] According to the invention, the particle size of the magnetic additive is generally selected in the range of 10-60 μm in order to achieve particularly high shielding in the magnetic field and at the same time very good distribution of the additive in the plastic matrix.
[0061] As shown in the embodiment further tabulated in Table 2a, the use of other particle sizes does not result in synergy according to the present invention.
[0062] The component made of the synthetic material and on which the EMI measurement is performed has a component thickness of 1 mm to 4 mm, preferably 2 mm to 3 mm.
[0063] Advantageously, the synthetic materials according to the invention can be used to make articles made of them or coated with them suitable for X-ray detection. Thus, articles made of the synthetic materials according to the invention or coated with them can advantageously be detected by hand luggage X-ray machines or conventional X-ray machines in medical practice.
[0064] For the use according to the invention of such detectable X-rays, the following magnetic additives are preferred:
[0065] 1) CuSn10 with uncertain particle shape, with a D50 value of 64.4 μm and a weight fraction starting from 20 wt %;
[0066] 2) 240 mesh CuZn30 with uncertain particle shape, with a weight fraction starting from 20 wt%;
[0067] 3) copper (II) oxide, with a D50 value of 23.9 μm and a weight fraction starting from 20 wt %;
[0068] 4) Natural magnetite, with a particle density of 5.2g / cm 3 , magnetite content ≥ 98.1%, D50 value 17 μm, weight fraction 20 wt % to 40 wt %;
[0069] 5) 325 mesh iron powder, the weight fraction of which is 20 wt % to 40 wt %;
[0070] 6) Gas atomized ferrite steel powder, with a weight fraction of 55 wt% to 80 wt% and a D50 value of 20-53 μm. DETAILED DESCRIPTION
[0071] The present invention is described in the following in a preferred embodiment in the form of tables, wherein the material composition of the synthetic material used as the base matrix and the magnetic additive or conductive additive mixed therein are listed respectively, and the advantageous properties of the corresponding components are listed respectively.
[0072] Each embodiment listed in the table below includes the base or matrix composite material used, the type of additive or additive mixture, the D50 value of the particle size and the weight fraction of the magnetic additive or conductive additive mixed in and their respective fractions. These composites from matrix composite materials and additives are used to produce sample objects with a wall thickness of 2 mm. The shielding of electric and magnetic fields is measured in principle on these 2 mm thick sample objects made of the corresponding composite materials, because this thickness is closest to the most common housing applications. The measurement is further carried out in close proximity to the sample.
[0073] Basic formula
[0074] Base Formulation 1 is PC-ABS weighing 100600 g.
[0075] Basic recipe 1 Weight [g] High impact ABS 48000 Low viscosity PC 52000 Lubricants 200 Processing Aids 400
[0076] Basic formula 2 is also PC-ABS, with a weight of 100100g, in which the matrix synthetic material already contains lubricant:
[0077] Basic recipe 2 Weight [g] PC-ABS 65∶35 100000 Antioxidants 100
[0078] Base formulation 3 is PA6, which weighs 101800 g and has the following composition:
[0079] Basic recipe 3 Weight [g] Type A PA6 (2.4 = NV) 100000 Lubricants 800 Antioxidants 1000
[0080] Base formulation 4 is a PA66 with the following composition, base formulation 4a is a PA66 weighing 102000 g, and base formulation 4b is a PA66 weighing 104242 g:
[0081]
[0082]
[0083] Base formulation 5 is PA6 with the following composition:
[0084] Basic recipe 5 Fraction Type A PA6 (2.9 = MV) 54.7% Antioxidants 0.5% Lubricants 0.3% pigment 1.0%
[0085] The basic formulations 6 and 6a are PA6.
[0086] Basic recipe 6 Weight [g] Type A PA6 (2.4 = NV) 100000 Intrinsic filler 20760 Lubricants 500 Antioxidants 500 pigment 2800 Basic Formula 6a Weight [g] Type A PA6 (2.4 = NV) 100000 Lubricants 500 Antioxidants 500 pigment 2800
[0087] The base formula 7 is PPS with a weight of 100900 g, and the base formula 7a is PPS with a weight of 101896 g:
[0088] Basic recipe 7 Weight [g] PPS(VISKO 50) 100000 Lubricants 600 pigment 300 Basic Formula 7a Weight [g] PPS 100000 Lubricants 610 pigment 1286
[0089] The magnetic and conductive additives used are in particular the following:
[0090] Magnetite has the composition of Fe3O4=Fe(II)Fe(III)2O4 and a spinel structure, as well as ferrimagnetic behavior.
[0091] Iron powder is ferromagnetic.
[0092] The composition of MnZn ferrite is Mn a Zn (1-a) Fe2O4.
[0093] Steel powder is a gas atomized ferrite powder with a particle size of 20-53 μm and is ferrimagnetic.
[0094] Plasticyl PCI501 is 15% MWCNT and CuSn10 is diamagnetic silver-coated copper.
[0095] Finely ground alumina Al2O3 is paramagnetic, and aluminum silicate Al2O3 SiO2 is paramagnetic.
[0096] Mica is a ferrimagnetic aluminum-iron greenstone K Al(Mg, Fe)[Si4O 10 (OH)2].
[0097] Dolomite CaMg(CO3)2 is paramagnetic.
[0098] AgCu20 is a diamagnetic, plate-shaped copper particle with a 20% silver coating and a D50 value of 8-13 μm.
[0099] Carbon gelege is a prefabricated part made from industrial waste with a mesh structure.
[0100] Manganese sulfate MnSO4 is paramagnetic.
[0101] Copper (II) oxide CuO with a D50 value of 23.9 μm is a diamagnetic ceramic and a semiconductor.
[0102]
[0103]
[0104]
[0105]
[0106]
[0107]
[0108]
[0109]
[0110]
[0111]
[0112] Table 2a, which contains examples not according to the invention, shows the importance of the particle size in addition to the examples listed in the table. A comparison of magnetite with a particle size according to the invention and magnetite with a particle size not according to the invention, with other parameters remaining constant, shows that, just as with the corresponding comparison with ferrites, too small a particle size leads to a reduced shielding effect in the magnetic field (H field) and thus to a composite not according to the invention. The table also shows that iron powder cannot simply be interchanged with an iron alloy, but that the type of magnetic additive has a great influence on the shielding behavior.
[0113] It has further been shown that when the additive particles are too large, shielding in the electric field decreases, which is especially evident in the comparison between magnetite and MnZn ferrite. This is probably due to the fact that the fiber extrusion causes disturbances in the carbon fiber network due to its size and mass.
[0114] Furthermore, it was shown that there is no correlation between shielding in the electric or magnetic field and the surface resistance. At almost the same resistance, shielding values in the electric field sometimes deviate strongly from each other.
Claims
1. A thermoplastic synthetic material comprising an admixed additive, wherein the thermoplastic synthetic material has a shielding behavior of more than 20 dB in a magnetic field and an electric field in the case of an object comprising the thermoplastic synthetic material, the wall thickness of the object being 1 to 4 mm, the shielding behavior being determined in an electric field in accordance with standard ASTM D4935 or IEC 62153-4-4Ed2, wherein the admixed additive is a first magnetic additive or a mixture of a first and a second magnetic additive or a mixture of a magnetic additive and a conductive additive, wherein the thermoplastic synthetic material is selected from the group consisting of copolymers of PA6, PA66, PPS, PC and ABS, characterized in that The thermoplastic synthetic material is PC+ABS, PPS or PA 6, and contains 70%-80% 325 mesh, D50≤45μm ferromagnetic iron powder as the first magnetic additive, or The thermoplastic synthetic material is PA66 and contains aluminum silicate with a D50 of 1.4 μm as a first magnetic additive and ferroaluminum chalcanthite with a D50 of 4.2 μm as a second magnetic additive, each in a weight fraction of 10 wt % to 20 wt %, or The thermoplastic synthetic material is PC+ABS and contains 15% carbon fiber and 40% magnetite with D50=17μm as combined additives, or the thermoplastic synthetic material is PA6 and contains 10wt% to 20wt% carbon fiber and 55wt% to 65wt% 325 mesh iron powder with D50≤45μm as combined additives.
2. The thermoplastic synthetic material according to claim 1, characterized in that The wall thickness of said object comprising said thermoplastic synthetic material is 2 mm.
3. Use of the thermoplastic synthetic material according to claim 1 for achieving X-ray detectability of objects made therefrom.
Citation Information
Patent Citations
UV-absorbent plastic composite, especially for production of food packaging film, contains finely-dispersed metal oxide, metal titanate or metal zirconate, e.g. titanium oxide or barium titanate
DE10008473A1
CONDUCTIVE POLYMER COMPOSITE, THREE-DIMENSIONAL PRINTING PROCESS AND FILAMENT
DE102017200448A1
Flame-retardant thermoplastic resin composition
EP1127917B1
Products manufacturing process for recycling wasteplastics
KR1020020068248A
Silicon carbide containing thermoplastic compositions, method of preparing, and articles comprising the same
WO2009083914A1